2009
DOI: 10.1016/j.njas.2009.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Testing different CO2 response algorithms against a FACE crop rotation experiment

Abstract: a b s t r a c tA soil-crop-environment model was used to describe the combined effects of atmospheric carbon dioxide concentration [CO 2 ], temperature and precipitation on different agricultural crop species. Within this model, a set of algorithms describing CO 2 response to photosynthesis and crop water use efficiency, which differed in complexity and parameter requirements, was tested for its suitability to explain crop growth responses and soil moisture dynamics observed over 6 years in a crop rotation (wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 58 publications
1
13
0
1
Order By: Relevance
“…Thus, by applying a 15-model ensemble (where most models used the approach of radiation use efficiency), we were able to reproduce the results generated in other modelling studies that simulated the effect similarly well (Kartschall et al, 1995;Nendel et al, 2009;Tubiello et al, 1999).…”
Section: Co 2 /Nitrogen/tillage/residuesmentioning
confidence: 91%
“…Thus, by applying a 15-model ensemble (where most models used the approach of radiation use efficiency), we were able to reproduce the results generated in other modelling studies that simulated the effect similarly well (Kartschall et al, 1995;Nendel et al, 2009;Tubiello et al, 1999).…”
Section: Co 2 /Nitrogen/tillage/residuesmentioning
confidence: 91%
“…In a comparison of several different approaches to determine photosynthesis rates in C 3 -plants against actual results from FACE experiments (Nendel et al, 2009), the approach suggested by HOFFMANN did show the best results when estimating dry matter, yield, LAI and soil moisture changes.…”
Section: Crop Modelmentioning
confidence: 99%
“…Kimball et al (1998) found a slight increase in ET in a FACE experiment over cotton fields, 20 but that increase was within the error of the ET estimation, and so was not deemed statistically significant. In contrast, Nendel et al (2009) found a decrease in ET, and an increase in dry above-ground biomass over a FACE crop rotation experiment. In this study, we found a decrease in ET.…”
Section: Discussionmentioning
confidence: 68%